Late Local Recurrence of Bone Giant Cell Tumors Associated with an Increased Risk for Malignant Transformation - Tsukamoto, Shinji (Cancers (Basel), 2021)
SIMPLE SUMMARY: In giant cell tumor of bone (GCTB), an intermediate malignant bone tumor, approximately 4% of cases can undergo malignant transformation. We analyzed risk factors for malignant transformation of GCTB treated without radiotherapy and retrospectively reviewed medical files of 461 patients with GCTB of the extremities who had undergone surgery alone, with no radiotherapy or denosumab therapy. Malignant transformation occurred in 15 of 461 patients (3.3%) at a median follow-up period of 192 months. The median follow-up duration was 89.4 months. Multivariate analysis revealed that local recurrence was an independent prognostic factor for unfavorable malignant transformation. The interval between the last surgery to local recurrence and malignant transformation was longer than that to local recurrence of benign GCTB, with a median of 15.2 (IQR, 5.2–25.4) years versus 1.3 (IQR, 0.8–2.6) months, respectively (p < 0.001). Late local recurrence of GCTB is associated with a higher risk of malignant transformation. ABSTRACT: In giant cell tumor of bone (GCTB), an intermediate malignant bone tumor, approximately 4% of all cases undergo malignant transformation. Accordingly, we analyzed risk factors for malignant transformation of GCTB treated without radiotherapy. We retrospectively reviewed medical records of 530 patients with GCTB of the extremities, admitted and treated at two institutions between January 1980 and December 2019. Overall, 4 patients with primary malignant GCTB, 4 patients with missing data, 3 patients with a history of radiotherapy, 22 patients with a follow-up of less than 6 months, and 36 patients who received denosumab were excluded. Accordingly, 461 patients were included for further analysis. Malignant transformation was observed in 15 of 461 patients (3.3%) at a median follow-up period of 192 months. The median follow-up duration was 89.4 months. Multivariate analysis revealed that local recurrence was an independent prognostic factor for unfavorable malignant transformation (Hazard ratio [HR], 11.33; 95% confidence interval [CI] 2.33–55.13; p = 0.003 for once versus none and HR, 11.24; 95% CI, 1.76–71.96; and p = 0.011 for twice or more versus none). The interval between the last surgery to local recurrence and malignant transformation was longer than that to local recurrence of benign GCTB, with a median of 15.2 years (interquartile range [IQR], 5.2–25.4) versus 1.3 months (IQR, 0.8–2.6), respectively (p < 0.001). Late local recurrence of GCTB is associated with a higher risk of malignant transformation.